Optimizing effervescent granules of butterfly pea (Clitoria ternatea L) flower ethanol extract as antioxidant - Suhesti, Tuti Sri; Warsinah, Warsinah; Wulandari, Pitra (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2022)
Background: Butterfly pea (Clitoria ternatea) contains secondary metabolites, including flavonoids, saponins, terpenoids, tannins, and anthocyanins which have antioxidant activity. Objective: This research aims to produce the effervescent granule preparations of the butterfly pea flower ethanol extract with the optimal concentrations of citric acid and tartaric acid. Methods: Butterfly pea flower was extracted using 70% ethanol. Effervescent granules were made using the wet granulation method in eight formulas containing citric acid and tartaric acid. The physical properties of granules were evaluated, including extract quality, flow rate, dissolution time, and pH. Results: The concentration of the mixed components of citric acid 48.65 mg and tartaric acid 576.30 mg was the most optimal combination of acid sources for effervescent granules of butterfly pea flower extract with a desirability value of 1,000. Conclusion: The variation in the concentration of citric acid and tartaric acid affected flow rate, dissolution time, and pH of the effervescent granule preparation.